The effect of Dadih for the prevention of iron deficiency anemia in adolescent girls 12-15 years old - Rena Budiyatri; Gemala Anjani; Anang Mohamad Legowo; Ahmad Syauqy; Edward Kurnia Setiawan Limijadi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Adolescent girls are at risk of developing iron deficiency anemia. Dadih has high nutritional value and iron and probiotics. This study aimed to analyze the effect of administering Dadih to prevent iron deficiency anemia in adolescent girls aged 12-15. This study used a randomized controlled trial pre-posttest group design, which consisted of an intervention and control group totalling 40 participants taken randomly at the Sumatera Thawalib Parabek Bukittinggi Islamic Boarding School from February to June 2023. In both groups, serum ferritin and hemoglobin levels were measured before and after treatment for 14 days. The intervention group was administered 100 g of Dadih 1x a day, and the control group was administered a placebo. Data analysis was performed using the Wilcoxon statistical and Paired T-test at a 95%CI. Results: There was a significant difference in the hemoglobin levels before and after treatment (p=0,003). There was no significant difference in serum ferritin levels before and after treatment (p=0,191). In conclusion, the administration of 100 g of dadih did not increase serum ferritin and hemoglobin levels, and the independent administration of 100 g of Dadih to prevent iron deficiency anemia still needs to be considered.